Prospects and barriers to postsocialist agricultural development: Case of Uzbekistan - Kwiecińska-Zdrenka, Monika; Hałasiewicz, Andrzej (Eastern European Countryside, 2024)
Almost 30 years after gaining independence from the Soviet Union, the government of Uzbekistan has initiated significant structural reforms, including agricultural reform, which are expected to result in a transition to the free-market system and an acceleration of development, among others. The change in development direction is accompanied by great interest from global and international organisations supporting developing countries (e.g. the World Bank, European Investment Bank, European Bank of Reconstruction and Development, Japan International Cooperation Agency and Islamic Development Bank, etc.). This study discusses the causes of implementing these reforms in Uzbekistan much later than in the countries of Central Europe and the former Soviet republics and the pitfalls faced by the agricultural reforms undertaken in the past five years.